The Malpractice Administration Procedure in the Vortex of Crime: An Indonesian Perspective and Its Comparison with Other Countries - Yeni Nuraeni; Alfies Sihombing Sihombing (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2024)
Medical malpractice has become a complex issue that extends to criminal law, having serious implications for health practitioners and patients. The legal argument in determining the elements of negligence and medical malpractice is based on the difference in interpretation between ordinary criminal offenses regulated in the KUHP and medical criminal offenses. Th e aim of this study is to explain the theory and legal analysis related to the handling of medical malpractice cases in Indonesia and its comparison with other countries. This research uses normative juridic methods. The outcome of this study is the need for reforms in handling alleged medical malpractice cases in Indonesia by considering the paradigms and concepts of other countries to protect patient rights and improve the quality of health services in reducing the risk of malpractice in Indonesia.